(untitled) (Tribhuvan University Journal of Microbiology, 2025)
Objectives: The study was conducted to enumerate and identify the airborne bacteria and fungi in the urban area of Kathmandu using the settle plate method and to determine the antibiotic susceptibility pattern of the identified bacteria. Methods: The cross-sectional study was done from March to May 2025. A total of 39 air samples were collected from 3 distinct sites: Asan, Kamaladi Ganesh Mandir, and Tri-Chandra Multiple Campus, with 13 samples from each site, using the gravity settle plate method in Nutrient Agar and Potato dextrose agar media at 37°C for 24 hours for bacteria and 28°C for 3-5 days for fungi and the research was carried out at the Department of Microbiology, Tri-Chandra Multiple Campus. Results: The bacterial load ranged from 640 to 4x104 CFU/m3, while fungal load ranged from 8.4x102 to 4.9x103 CFU/m3. The dominant bacterial isolates were Micrococcus spp. (25.17%), followed by Bacillus spp. (21.79%), S. aureus (19.05%), E. coli (18.37%), and Klebsiella spp. (15.65%), whereas Aspergillus spp. (21.4%) was the most dominant fungi followed by Fusarium spp. (18.25%), Penicillium spp. (15.9%), Cladosporium spp. (15.1%), Mucor spp. (14.3%), Rhizopus spp. (8.7%), and Alternaria spp. (6.4%). Conclusion: The present study shows that air contains various bacteria and fungi, which can be harmful to human health. It highlights the need to reduce air pollution and raise public awareness.